Método das equivalências aplicado a placas esconsas - Bispo, Sonia Ribeiro Almeida (1976)
The purpose of this work is to obtain comparative results by the numerical methods of equivalences, finite differences and finite elements, applied to several cases of skew plates with built in edges. Convergence towards the analytic solution has been examinated for different skew angles, and a study of time increasing with the number of joints has been performed for the methods of equivalences and finite differences. An automatic program was elaborated using the equivalence method, and another using the finite difference method. For the finite element method the ICES STRUDL II program was used. Results given by equivalence method had good accuracy when compared to analytical and other numerical solutions.